Konservasi Lingkungan Berbasis Kearifan Lokal di Kampung Adat Kuta Ciamis - Lia Yulisma; Feri Bakhtiar Rinaldi (Universitas Sebelas Maret, 2025)
A deeper understanding of local wisdom in the Kuta Traditional Village is expected to be the basis for developing more adaptive and sustainable conservation strategies, as well as making a real contribution to environmental conservation in Indonesia. This study aims to explore the role of local wisdom in environmental conservation. This study uses a qualitative approach with a case study method, involving in-depth interviews, observations, focus group discussions (FGD), and document analysis. The sources in this study were the Head of Kuta Village Customary, kuncen, administrators, and the community of Kuta Traditional Village. The focus of the study includes identifying forms of local wisdom in the fields of Natural Resource management, water management, waste management, and climate change, analysis of conservation practices, challenges faced in implementing local wisdom, and its impact on environmental sustainability. The Kuta Traditional Village community has rich local wisdom in natural resource management, water management, waste management, and environmental conservation. However, to maintain these practices amidst modern challenges such as climate change and external pressures, continuous education, technological adaptation, and strong collaboration are needed. With joint efforts, communities can continue to preserve their environment in a way that is sustainable and relevant to current developments.